2016
DOI: 10.1021/acsami.5b11016
|View full text |Cite
|
Sign up to set email alerts
|

Versatile Types of MRI-Visible Cationic Nanoparticles Involving Pullulan Polysaccharides for Multifunctional Gene Carriers

Abstract: Owing to the low cytotoxicity and excellent biocompatibility, polysaccharides are good candidates for the development of promising biomaterials. In this paper, a series of magnetic resonance imaging (MRI)-visible cationic polymeric nanoparticles involving liver cell-targeting polysaccharides were flexibly designed for multifunctional gene delivery systems. The pullulan-based vector (PuPGEA) consisting of one liver cell-targeting pullulan backbone and ethanolamine-functionalized poly(glycidyl methacrylate) (den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 50 publications
2
47
0
Order By: Relevance
“…The structures of polysaccharides vary considerably but span from linear to highly branched polymers with molecular weights ranging from thousands to millions, composed of mono‐ or disaccharides, or short‐chain oligomers bound together by glycosidic linkages . There is a rich history of research on the use of polysaccharides in a range of therapeutic applications including: i) soft tissue engineering, where the materials can be designed to mimic the mechanical properties of the extracellular matrix in the tissue; ii) as drug, protein, or gene delivery systems, where polysaccharides have a large number of reactive groups that allow for tunable properties such as pH‐responsiveness; and iii) as nanoprobes for cellular and tissue imaging . Of the available polysaccharides, the most studied biopolymers for use as therapeutic materials are arguably derivatives or composites of cellulose, chitosan, hyaluronic acid, and/or alginate .…”
Section: Introductionmentioning
confidence: 99%
“…The structures of polysaccharides vary considerably but span from linear to highly branched polymers with molecular weights ranging from thousands to millions, composed of mono‐ or disaccharides, or short‐chain oligomers bound together by glycosidic linkages . There is a rich history of research on the use of polysaccharides in a range of therapeutic applications including: i) soft tissue engineering, where the materials can be designed to mimic the mechanical properties of the extracellular matrix in the tissue; ii) as drug, protein, or gene delivery systems, where polysaccharides have a large number of reactive groups that allow for tunable properties such as pH‐responsiveness; and iii) as nanoprobes for cellular and tissue imaging . Of the available polysaccharides, the most studied biopolymers for use as therapeutic materials are arguably derivatives or composites of cellulose, chitosan, hyaluronic acid, and/or alginate .…”
Section: Introductionmentioning
confidence: 99%
“…Due to its liver specificity, pullulan was widely exploited for liver‐targeting drug or gene delivery . In our previous study, we observed pullulan‐containing vectors could effectively mediate gene delivery in liver cells . Herein, we investigated whether there was in vivo liver specificity for pullulan‐containing PuPGEA2 in mice.…”
Section: Resultsmentioning
confidence: 97%
“…The reaction time was adjusted to obtain different molecular weight PuPGMAs (Table S1, Supporting Information). The final PuPGEA products were harvested via ring‐opening reaction of PuPGMA with excess EA at 50 °C for 48 h. All the above synthesis procedures were described in detail previously . PuPGEAs with two molecular weights are denoted as PuPGEA1 and PuPGEA2, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations